In defence of the faith : Joaquim Marques de Araujo, a comissario in the age of Inquisitional decline - Wadsworth, James E., 1968- (McGill-Queen's studies in the history of religion., 2013)
Recounting an insider's perspective of the turbulent historical currents of late eighteenth-century Brazil.